2020
DOI: 10.3389/fmicb.2020.02062
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Competitions Reveal Determinants of Plasmid Evolutionary Success

Abstract: Plasmids are autonomously replicating genetic elements that are ubiquitous in all taxa and habitats where they constitute an integral part of microbial genomes. The stable inheritance of plasmids depends on their segregation during cell division and their longterm persistence in a host population is thought to largely depend on their impact on the host fitness. Nonetheless, many plasmids found in nature are lacking a clear trait that is advantageous to their host; the determinants of plasmid evolutionary succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Regarding plasmids, which are mobile genetic elements harboured by prokaryotic cells, they replicate independently of the chromosome and act as a major driving force in prokaryotic diversity, evolution and fitness 50 , 51 . In this study, we identified 41 plasmids in members of the Rickettsia genus.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding plasmids, which are mobile genetic elements harboured by prokaryotic cells, they replicate independently of the chromosome and act as a major driving force in prokaryotic diversity, evolution and fitness 50 , 51 . In this study, we identified 41 plasmids in members of the Rickettsia genus.…”
Section: Discussionmentioning
confidence: 99%
“…Epistatic interactions between MGEs can determine the fate of the MGE in bacterial populations, promoting low-fitness-cost associations and long-term maintenance, thus shaping the highways of AMR genes (752,933,934). Plasmid evolutionary success and the plasmid-mediated spread of AMR are to a significant degree the result of a intracellular plasmid competition with other plasmids, influencing the spread by lateral transfer, in particular, the stable plasmid inheritance (incompatibility) (935). Conjugative plasmids commonly encode fertility inhibition determinants, which reduce the conjugation frequency of other plasmids present in the same cell (936).…”
Section: Barriers Determined By the Interactions Between Mobile Genetic Elementsmentioning
confidence: 99%
“…Nonetheless, the stability of plasmid vertical inheritance is paramount for plasmid survival and long-term evolution (reviewed in [ 75 ]). The potential deleterious effect of ABR gene acquisition in plasmid genomes on the plasmid fitness [ 76 ] may explain the rarity of ABR genes on plasmids ( figure 1 ), specifically in non-mobile plasmids [ 73 ].…”
Section: Discussionmentioning
confidence: 99%